Alteration of Plasma Amino Acid Concentrations in Iranian Children with COVID-19 - Sedigheh Shams; Aileen Azari-Yam; Moeinadin Safavi; Zahra Zamani; Maryam Sotoudeh-Anvari; Meisam Sharifzadeh Ekbatani; Mohammad-Taghi Haghi-Ashtiani; Fatemeh Mozafari; Bahareh Yaghmaie; Leila Shafeghat (International Journal of Pediatrics)
COVID-19 is an acute viral disease that has so far infected more than 200 million and killed more than four million worldwide. It affects the immune system and other organs. Here, we investigated the level of free plasma amino acids in COVID-19 patients and compared them with non-COVID-19 subjects. We also compared amino acids levels in critically ill patients admitted to the intensive care unit (ICU) with non-ICU patients and expired and recovered patients. Twenty-six COVID-19 patients and 32 non-COVID-19 subjects were included in the study. The mean of glutamic acid, serine, glycine, threonine, phenylalanine, leucine, lysine, alanine, arginine, aspartic acid, and ornithine was significantly higher in cases than controls. In addition, the mean of glutamine was significantly lower in patients than controls (443.89±254.31 vs. 651.73±107.38, PV<0.001). Low level of glutamine and isoleucine was seen in the majority of ICU and expired patients, respectively. Logistic regression analysis showed low level of isoleucine as a predictor variable in mortality (P=0.02, EXP B=16.5, and CI 95%=1.48,−183.07). There was a positive and significant relationship between some amino acids levels, serum liver enzymes, and sodium concentrations. There was also a significant but negative correlation between histidine levels, ESR, and ferritin. Phenylalanine had a highly positive relationship with serum procalcitonin in patients (R2=0.534, PV=0.015). Our studies have shown the alteration of plasma amino acids concentration in COVID-19 patients. These changes are more evident in critically ill and at-risk patients.